Hubungan faktor manusia, organisasi, dan teknologi dengan penggunaan aplikasi satu sehat pada tenaga kesehatan di puskesmas - Elda Oktavia; Rumita Ena Sari; Adila Solida; Arnild Augina Mekarisce (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: The implementation of the one health program in community health centers still faces various specific challenges, including limited resources and differences in digital literacy among health workers, with relatively low utilization rates, which have the potential to hinder the achievement of health resources target. Purpose: To analyze the relationship between human, organizational and technological factors with the use of the one healthy application among health workers at community health centers. Method: This study employed a quantitative approach with a cross-sectional design. The sample size was 105, selected using random sampling. Data were collected through questionnaires and then analyzed using univariate, bivariate and multivariate methods. Results: The proportion of users of the One Healthy application was 57.4%. The results of the study showed a relationship between system use(p=0,000), information quality(p=0,000), and net benefit (p=0,006) with the use of the One Healthy application. Meanwhile, user satisfaction(p=0,066), organizational structure(p=0,658) and organizational environment(p=0,101), system quality(p=0,781), and service quality(p=0,653) did not show a relationship with the use of the One Healthy application among health workers in community health centers. Conclusion: There is a relationship between system use, information quality, and net benefit with the use of the SATU SEHAT application. Meanwhile, user satisfaction, organizational structure and environment, system quality, and service quality do not show any relationship with the use of the SATU SEHAT application.   Keywords: Hot-Fit Model; Human Factors; Healthcare Workers; Primary Healthcare Center; Satu Sehat Application.